ASSESSMENT OF DEAF-DUMB TEACHERS PERFORMANCE REGARDING HEALTH PROTECTIVE BEHAVIORS IN THE MIDDLE EUPHRATES CITIES (World Bulletin of Public Health, 2022)
Health protective behavior is not a new topic, but at the present time take the place of importance among policy makers, and developed several future programs to assess trends to work towards the protective behavior of health from chronic diseases and permanent disability
Keywords: Teachers Performance; Deaf-Dumb students; Health Protective behaviors